THE ROLE OF ORGANIZATIONAL STRUCTURE IN IMPROVING HUMAN RESOURCES - Hussein Abd Hamad; Hassan Farhan Ahmed; Hashem Rashid Ajrash (Scholars Digest Publishing, 2024)
This study aims to determine the role of organizational structure in improving human resource management in Salah al-Din Governorate. To achieve the objectives of the study, a questionnaire was developed and distributed to a random sample of employees in the Salah al-Din Provincial Office (80). A number of results were obtained, the most important of which are. There is a positive relationship between strategic direction and human resource management, and there is a positive relationship between flexibility and human resource management at the 0.05 significance level. Based on these findings, a number of recommendations are made, the most important of which are as follows: It may be necessary to reorganize the organization to improve the consistency and coordination of activities and tasks. This may include structural reorganization and effective distribution of tasks and responsibilities.
Keywords: structure, human resources management, Salah al-Din Governorate Office.